WILAYAH YANG BERUBAH: Transformasi Hunian dengan Perspektif Spasial dan Tatanan Budaya Sebagai Potensi Destination Branding Kota Tua Ampenan Mataram - Mihardja, Eli Jamilah; Ihsan, Mohammad; Adriati, Fatin (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2019)
Identification of changes in the culture of society in the Kota Tua Ampenan Mataram (the Old Town of Ampenan) is expected to be able to influence the emergence of residential transformation so that destination branding strategies can be developed. This research combines the heritage engineering approach in guiding the destination branding strategy. Using data collection methods through field observations and interviews with community leaders, elders, and the community, findings showed that the heritage engineering approach resulted in a recommendation that the Kota Tua Ampenan could be developed into a specific residential area and become a city identity. Therefore, it is necessary to develop cultural changes in the local community, such as changes in mindset, perspective, community behavior, and agreements between communities. This is important to develop Kota Tua Ampenan as the flagship destination of Mataram, NTB. To cite this article (7th APA style): Mihardja, E. J., Ihsan, M. & Adriati, F. (2019). Wilayah yang Berubah: Transformasi Hunian dengan Perspektif Spasial dan Tatanan Budaya sebagai Potensi Destination Branding Kota Tua Ampenan Mataram [Residential Transformation with Spatial and Cultural Perspectives as Destination Branding Potential]. Journal Communication Spectrum, 9(1), 67-78. http://dx.doi.org/10.36782/jcs.v9i1.1938